Monte Carlo simulation of magnetic properties of a ferrimagnetic nanoisland with hexagonal prismatic core-shell structure. (January 2018) - Wang, Wei; Peng, Zhou; Lin, Shan-shan; Li, Qi; Lv, Dan; Yang, Sen
Abstract: Using Monte Carlo simulation, the magnetic and thermodynamic properties of a ferrimagnetic nanoisland with hexagonal prismatic core-shell structure, consisting of the bilayer with a core of spin-5/2 atoms surrounded by shell of spin-2 atoms in the external magnetic field have been studied. We have investigated the effects of the single-ion anisotropies, the exchange coupling and the magnetic field on the magnetization, susceptibility, internal energy and blocking temperature of the nanoisland. A great number of interesting behaviors, such as various types of magnetization curves, have been obtained depending on different values of the physical parameters. The magnetic hysteresis loop behaviors are the main focus of the research. The system exhibits multiple hysteresis loop behaviors, such as double, triple and quadruple hysteresis loops for certain parameters. Highlights: A hexagonal prismatic core-shell ferrimagnetic nanoisland with spin-2 and spin-5/2 has been proposed. Effects of the single-ion anisotropies, the exchange couplings and temperature on magnetic properties have been investigated. Magnetization, susceptibility and internal energy have been discussed. The phase diagrams in different parameter planes were obtained. Multiple hysteresis loops behaviors such as double, triple and quadruple hysteresis loops have been discovered.